The Analysis of Creativity's Correlation and Contribution toward UNNES Biology Teacher's Candidate Intention to Become Teacherpreneur - Handayani, Defi Fina; Ridlo, Saiful (FMIPA UNNES, 2020)
In the industrial revolution 4.0 era, the improvement in the quality of human resources is the concern of all parties. The integration of entrepreneurship education in science education can improve the quality of education. Innovative individuals begin with high creativity. Teacher candidates who have creativity can be involved in entrepreneurship and can increase the intention to become teacherpreneur. The purpose of this study is to determine the relationship between creativity with the intention of becoming a teacherpreneur on UNNES Biology teacher candidates. The quantitative research is analyzed by ex-post facto research strategy. The population in this study are UNNES Biology Education students for 2015, 2016 and 2017. The study sample consists of 190 students which are determined by proportional random sampling. The creativity of teacher candidates is measured by the scale of creativity. Whereas the intention to become a teacherpreneur is measured by the intention to become a teacherpreneur scale. The results of research data analysis using Pearson product-moment correlation technique with the help of SPSS. From the calculation results, it is known that the Sig. is obtained at 0,000 < 0.05 with a correlation value of 0.432 (included in the medium category) shows a significant positive relationship between creativity and intention to become teacherprenenur. The contribution of creativity to the intention to become teacherpreneur is 18.5%. Creativity has a positive and significant effect on the intention to become teacherprenenur. The obtained regression equation is Y = 162,759 + 2,132X